Determination and analysis of gene expression involved in glucose metabolism under the conditions of the development of experimental diabetes of dexamethasone type (type 2 diabetes) - T. V. Ivanenko; A. V. Vynokurova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Type 2 diabetes is one of the most common and serious chronic diseases today, which has become a global health care problem. Type 2 diabetes accounts for about 90–95 % of all cases of diabetes and significantly affects patients’ quality life due to the development of numerous complications, such as cardiovascular diseases, chronic renal failure, retinopathy, neuropathy. Modern research in the field of diabetology pays considerable attention to the understanding of the genetic mechanisms of the pathogenesis of type 2 diabetes, which makes it possible to develop new approaches to its diagnosis and treatment. Individualization of laboratory diagnostics and treatment, which considers the genetic, metabolic and clinical characteristics of each patient, is a key direction in improving the effectiveness of the treatment of type 2 diabetes. Type 2 diabetes is a complex polygenic disease, that develops under the influence of both genetic and external factors, which requires an integrated approach to its diagnosis, treatment and prevention. Taking into account the constant increase in the prevalence of this disease, the relevance of scientific research in this area is beyond doubt. The development of new pharmacological agents, improvement of laboratory diagnostic strategies and individualization of treatment are key directions for overcoming the problem of type 2 diabetes and improving the quality of life of patients.